DAMPAK PEMBELAJARAN ONLINE TERHADAP PERKEMBANGAN KOGNITIF PESERTA DIDIK KELAS XI SMAK SANTO FRANSISKUS ASISI LARANTUKA TAHUN AJARAN 2021/2022 - Bhoki, Yuliana K; Ngongo, Maria Hendritha Lydia; Bele, Graciana Amanda; Oetpah, Dorince (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2022)
This research was conducted with the aim of knowing the impact of implementing online learning on the cognitive abilities of students in class XI SMAK St. Francis of Assisi Larantuka. This study uses a qualitative method. The informants in this study consisted of students, homeroom teachers, subject teachers, and parents. Data collection techniques used interviews and documentation studies, while data analysis techniques consisted of data collection, data reduction, data presentation, and data verification. The results of the study showed that the cognitive development of students in class XI SMAK St. Francis of Assisi Larantuka while participating in online learning was very low. The influencing factors are the learning methods applied by the teacher, infrastructures such as gadgets, data pulses, networks, parental support, and attention and awareness of the students themselves being less than optimal. The efforts made are that teachers need to prepare creative and innovative learning using relevant methods in accordance with science and technology developments, provision and assistance of learning facilities for students, and regular evaluation of the entire learning process that has been implemented.